Human Health Risk Assessment of Nitrate-Contaminated Groundwater in North East Alluvial Plains of India - Ajeet Kumar; Sanjay Kumar Singh; Sunita Kumari Meena; S.K. Sinha; Lalita Rana; Amrita Kumari; A.K. Singh; Amrendra Kumar (Geography, Earth Science and Environment: Research Highlights Vol. 2, 2024)
The present study highlights about human health risk assessment of nitrate-contaminated groundwater in North East Alluvial Plains of India. Groundwater is a vital natural resource that provides nearly half of the world’s drinking water and plays a crucial role in food production. Nitrate that has accumulated in soils is highly prone to leaching, which is directly threatening the quality of groundwater. However, consuming water with high nitrate concentrations can have immediate effects on infants, leading to a condition called methemoglobinemia, where the blood is unable to carry sufficient oxygen to the body’s cells. Given the varying nitrate concentrations in water, it is important to study its undesirable effects. In rural areas, groundwater contamination is often linked to the excessive use of chemical fertilizers by local farmers. Shallow groundwater is essential for water use and maize yield, with nitrogen application significantly impacting crop uptake and water utilization from irrigation, though the specifics of groundwater use are less understood. Farmers in the region are applying an average of 278 kg/ha of nitrogen to Kharif maize, which is approximately 131.72% more than the recommended dose of 120 kgN/ha. The mean nitrogen application ranges from 251 to 323 kg/ha, with the highest application rates observed in Khagaria (323 kg N/ha), followed by Madhepura (275.08 kg N/ha), and the lowest in Saharsa (251.16 kg N/ha). The nitrogenous fertilizer application rates vary from 109.25% to 169.16% over the recommended dose, resulting in nitrate leaching. In this study, groundwater and surface water samples were collected from 12 villages, and various quality parameters were analyzed. Nitrate levels in groundwater ranged from 1.87 to 6.19 mg/L, while in surface water, they ranged from 1.87 to 3.84 mg/L, with the highest nitrate concentrations found in the Madhepura district. High intensive double or triple cropping system of the area has mostly utilized the leached nitrate through the ramified root system of the intercrops. The study assessed nitrate leaching in soil, groundwater contamination levels, and human health risks through chronic daily intake of nitrate and Hazard Quotient (HQ) values in the Khagaria, Saharsa, Madhepura, and Supaul districts of the eastern alluvial region of Bihar. It is time to be cautious to refrain away from the use of heavy doses of nitrogenous fertilizer by the farmers of the study area. Further studies on actual records of NO3 toxicity in residents are needed to validate the result of the present finding.